2003
DOI: 10.4028/www.scientific.net/kem.254-256.667
|View full text |Cite
|
Sign up to set email alerts
|

Tricalcium-Phosphate/Hydroxyapatite Bone Graft Extender for Use in Impaction Grafting Revision Surgery – an In Vitro Study in Human Femora

Abstract: Impacted morsellised allografts have successfully been used to address the problem of poor bone stock in revision surgery. However, concern exists about pathogen transmission, high cost and shortage of supply of donor bone. Bone graft extenders, such as tricalciumphosphate (TCP) and hydroxyapatite (HA), have been developed to minimize the use of donor bone. In a human cadaver model we evaluated the surgical and mechanical feasibility of a TCP/HA bone graft extender during impaction grafting revision surgery.TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Tricalcium phosphate and HA composite granules or HA granules are mixed with bone particles. Mechanical tests suggest tricalcium phosphate/HA granules (size, 2-4 mm) with a 50% mixture to allograft provided higher initial mechanical stability in axial compression testing [2,22] and impaction grafting using HA granules (size, 0.3-4 mm) with a 50% mixture provided greater rotational stability [8]. Our data suggest the effectiveness for the initial stability of the stem fixed by impaction grafting with HA granules was more obvious with the torsional test.…”
Section: Discussionmentioning
confidence: 77%
“…Tricalcium phosphate and HA composite granules or HA granules are mixed with bone particles. Mechanical tests suggest tricalcium phosphate/HA granules (size, 2-4 mm) with a 50% mixture to allograft provided higher initial mechanical stability in axial compression testing [2,22] and impaction grafting using HA granules (size, 0.3-4 mm) with a 50% mixture provided greater rotational stability [8]. Our data suggest the effectiveness for the initial stability of the stem fixed by impaction grafting with HA granules was more obvious with the torsional test.…”
Section: Discussionmentioning
confidence: 77%
“…Another study used a cemented model to look at a mixed tricalcium phosphate/HA substitute (BoneSave, Stryker Howmedica Osteonics). 31 It also found less subsidence with 50% graft substitute than with pure allograft (0.99 mm and 2.31 mm, respectively). This experiment did not look at higher mix ratios, and subsidence at the individual prosthesis-cement and cementfemur interfaces was not determined.…”
Section: Discussionmentioning
confidence: 91%
“…11 A study using a more realistic cemented femoral model also suggested that a tricalcium phosphate/ hydroxyapatite (HA) graft substitute decreased subsidence. 31 It is not known whether other graft substitutes have similar effects, or if the effects depend on the proportion of allograft to substitute. The mechanism by which graft substitutes reduce subsidence is also unknown.…”
mentioning
confidence: 99%
“…van Haaren et al 13 also reported that the mean impact forces were 12000-13000 N in the cadaver study. The measured impact forces in their studies were about five times higher than the impact force at the final rasping in our study.…”
Section: Discussionmentioning
confidence: 92%